(untitled) (International Journal of Engineering and Computer Science, 2017)
There is an urgent need for improving security in banking region. In this paper discussion is made about the face recognition technology, an important field of biometrics which will be employed for the purpose of checks on frauds using ATMs. The recent progress in biometric identification techniques, has made a great efforts to rescue the unsafe situations at the ATM. Several facial recognition techniques are studied which include two approaches, appearance based and geometric based. A new facial recognition technique: 3-D technique is also reviewed in the paper. These techniques are widely used in e-passports and on the airports for entry of travellers and others. ATM systems today use no more than an access card and PIN for identity verification. If the proposed technology of facial recognition becomes widely used, faces would be protected as well as PINs.